Effect of Guava Extract Administration on Megakaryocytes Amount in Mice Femur - Atik, Nur; Munawir, Maqrizi D. S.; Tarawifa, Susan; Darmadji, Hartati P. (Indonesian Journal of Clinical Pharmacy, 2017)
Dengue fever is a disease spread by mosquitoâs bite. Dengue fever is marked by the presence of thrombocytopenia. Traditional crops such as guava are commonly used to treat dengue fever. This research aims to know the effect of guava extract administration towards megakaryocytes amount in mice femur. The study was conducted at the Laboratory of Pharmacology and Therapy, Histology Laboratory of Faculty of Medicine at Universitas Padjadjaran, Eijkman, Bandung from September until November 2016 using laboratory experimental study design. 20 Swiss webster mice strains were divided randomly into 4 groups. Group I and II were administered quinine 2.8 mg/20 grBW/day for 14 days to decrease amount of trombocytes. Group II and III were administered guava extract 0.785 mg/20 grBW/day for 5 days. Group IV was administered aquadest for 19 days. In the 27th day, the mice left femurs were collected and made into paraffin section preparations with hematoxylin-eosin staining and then observed under microscope. Group IV had the most megakaryocytes followed by Group II, III, and I. Based on Kruskal-Wallis test, a significant difference was shown (p<0.05). Mann- Whitney test showed that there were significant differences between Group I and Group II, III, and IV. Meanwhile there was no significant difference between normal mice and extract-given mice. Guava extract is proven statistically significant to increase the megakaryocytes amount in thrombocytopenic mice without increasing number of megakaryocytes in normal mice.